Role of Watershed Management for Reducing Soil Erosion in Ethiopia - Tilahun, Zewde Alemayehu (International Journal of Scientific Research in Civil Engineering, 2019)
Watershed management implies the wise use of natural resources like land, water and biomass in a watershed to obtain optimum production with minimum disturbance to the environment Soil erosion is the main cause of land degradation that affects soil properties and ecosystems in Ethiopia. The Ethiopian highlands have been experiencing declining soil fertility and severe soil erosion due to intensive farming on steep and fragile lands and other factors attributed to population pressure. Ethiopia has a history of watershed management initiatives dating back to the 1970s. The present government started community based integrated watershed management practice. Keeping these in view the study entitled “Watershed Management in Highlands of Ethiopia: Soil conservation in Ethiopia is therefore not only closely related to the improvement and conservation of ecological environment, but also to the sustainable development of its agricultural sector and its economy at large. Ministry of Agriculture and Rural Development in collaboration of donor agency such as world food program in Amhara, Oromia, and Tigray National Regional state various conservation and rehabilitation of natural resource were implemented as a result positive impact were achieved. The watershed management practices played a crucial role in arresting runoff and help to reduce erosion hazard. In view of that at the pilot watershed level a total of 297 km hillside, 27,783 trenches, 446 m3 Gabion, 3167 m3 stone check dam, and 854 m3 sediment storage, 586 m3 gully rehabilitation/re-vegetation, 80 ha bund stabilization, 25 km construction of recharge pits have been constructed over the degraded hillsides. Watershed management is practiced as a means to increase rain fed agricultural production, conserve natural resources and reduce poverty in the highlands of Ethiopia which are characterized by high soil erosion, and severe natural resource degradation. Community participation should be improved by giving recognition to environmental, economic and social issues while planning and implementing watershed management